Exploring the Issues Surrounding Clinical Exome Sequencing in the Prenatal Setting. Issue 5 (10th March 2018) - Narayanan, Swetha; Blumberg, Bruce; Clayman, Marla L.; Pan, Vivian; Wicklund, Catherine
Abstract: Exome sequencing is a clinical diagnostic test offered primarily for children and adults with suspected genetic conditions. The purpose of this study was to explore issues related to exome sequencing in a reproductive clinical setting. This was a qualitative study using semi‐structured interviews. Participants were professionals drawn from four key stakeholder groups—healthcare providers, laboratory/industry, ethics, and government. Transcribed interviews were analyzed for emergent themes. Most participants saw potential clinical utility in offering prenatal exome sequencing for diagnostic purposes as opposed to screening. Participants expressed similar challenges already encountered with using exome sequencing in a pediatric setting, such as difficulty interpreting results and voiced many of the same concerns posed by prenatal testing, such as adequate pretest counseling. While previously reported issues and challenges were mentioned, participants agreed those difficulties are anticipated to be much greater with prenatal exome sequencing because of the scope of testing and the option for pregnancy decision‐making. The results of this study help gain a better understanding of the implications of using exome sequencing in a prenatal setting. Development of guidelines is also warranted to aid clinical practice and laboratory standards for reporting prenatal results.